PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PENERAPAN SISTEM PENGENDALIAN INTERN PEMERINTAH, DAN PENERAPAN STANDAR AKUNTANSI PEMERINTAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH KOTA PADANG - Bayu Dharma Putra; Syamsul Amar (Jurnal Riset Manajemen Bisnis dan Publik, 2015)
This study aimed to analyze the effect of human resource competencies, the implementation of internal control government system, and the government's application of accounting standards for financial reporting quality Padang city government. This research is quantitative research that is causative. The population in this study all accounting entities in the local government area of ​​Padang who are 45 Regional Working Units (on education) consists of 7 (seven) agencies and technical institutions, 18 (eighteen) service, the Regional Secretariat, Parliament Secretariat, 6 (six) office, 1 (one) and 11 district hospitals with the respondent is Penatausaha Financial Officer (CO) of each on education. Sampling technique using total sampling. The data analysis technique used is the path analysis (path analysis) using SPSS version 15.00. The results based pathway analysis showed that: (1) variable competence of human resources at 8.12% direct effect, indirect effect of 4.84% through the implementation of the SAP, and the indirect effect of 2.44% through the implementation of the SPIP quality of government financial statements, (2) the application of variable SPIP by 7.45% direct effect and indirect effect of 3.66% on the quality of government financial statements. (3) the implementation of SAP Variable 15.05% direct effect on the quality of government financial statements, while 58.40% is influenced by other factors outside the study. Keywords:    human resource competencies, implementation of internal control government system, and the government's application of accounting standards on the quality of government financial statements